Effects of Bi Addition on Si Features, Tensile Properties and Wear Resistance of Hypereutectic Al-15Si Alloy - Pereira,Cleiton Luiz (2020)
Bismuth (Bi) alloying in Aluminum (Al) alloys is considered of importance in special applications requiring improvements in the alloy machining. Despite that, the influence of Bi either on evolution of the solidification or on resulting microstructure of hypereutectic Al-Si alloys is still to be determined. The present research work is devoted to these requirements. In the present study, Al-15wt.% Si hypereutectic alloy is modified with 1.0 wt.% Bi. The effects of this addition on the morphology of the phases forming the microstructure and on the tensile/wear properties are investigated. Various samples characterized by distinct cooling rates are generated by transient directional solidification of the ternary Al-Si-Bi alloy. Microstructure is examined by optical microscopy and scanning electron microscopy (SEM) analyses, segregation by energy-dispersive X-ray spectroscopy (EDS) whereas wear and tensile properties have been characterized by standardized tests. The experimental variations of the eutectic spacing are compared to each other based on their trends. It is found that the addition of minor Bi content (~1 wt. %) permitted tensile strength and ductility of 195 MPa and 14%. Furthermore, wear resistance is improved by up to 20% due to the Bi addition. The reasons for that will be outlined.